Dispersion and Deposition of Fine Particles - Part I Wind Tunnel Experiments - K. Bode; R. V. Ramani (The National Institute for Occupational Safety and Health (NIOSH), 1995)
"IntroductionThe theory of particle dispersion and deposition in turbulent flow is important to many fields of science and engineering. Dispersion has been studied in some detail since the early fifties (Taylor, 1954; Fischer, 1967; Osipov and Grekov, 1968; Skobunov, 1970 and 1973; Klebanov and Martynyuk, 1974). A broad research effort has also been underway in studying the mechanics of dry particle deposition. Friedlander and Johnstone (1957) proposed a theory, according to which particle deposition from vertical pipe flow could be described by an eddy diffusion transport followed by a final flight to the surface. There have been numerous revisions and additions to this original theory (Owen, 1960; Liu and Agarwal, 1974; Liu and llori, 1974; El-Shobokshy and Ismael, 1980) The mining process essentially consists of breaking in situ materials and transporting them out of the mine. An inherent characteristic of this process is the generation of fine particles. Fine airborne particulates are associated with a number of threats to the health of the miners; fine coal dust can also result in mine-wide catastrophic incidents such as dust explosions. For these and other reasons, it is important to understand the behaviour of airborne dust particulates, particularly their generation, entrainment, transport, dispersion, and deposition in the mine environment for their control.Mine related studies on dispersion and deposition have been few. Yet, several studies of gas and dust dispersion, diesel exhaust contamination, and methane ingress into mine workings have recognized the need for developing reliable parameter values for fundamental understanding of the phenomena (Da""Yes and Slack, 1954; Hodkinson, 1957; Hodkinson and leach, 1958; Mass and Wildschut, 1966; Airey, 1969; Courtney et al., 1986; Stefanko, Ramani, and Thakur, 1974; Stefanko, Ramani and Kenzy, 1977; Bhaskar, 1987, Bhaskar and Ramani 1990; Qin and Ramani, 1989; Shankar and Ramani, 1990)."